Metodologia híbrida para caracterização da rede através da avaliação do desempenho da cadeia de suprimentos da construção civil - Volski, Isabela (2017)
The construction networks formation is an alternative to leverage project productivity through the joint work of the companies that make up it, that is, of its supply chain. In this sense, the research's objective is to propose a methodology to characterize the network formed for construction projects through the supply chain performance analysis. The method used consisted of a systematic bibliographic review, to delimit the networks formation factors and their respective supply chain performance variables. The data were obtained through the application of a structured questionnaire based on the use scale of these variables, which provided the supply chain performance indicators in a construction project. The methodology proposed for validation was applied in a network, whose participating companies are located in Concórdia city, Santa Catarina state, Brazil. To analyze the data, the multivariate analysis technique denominate clusters analysis was used, in order to verify the network homogeneity about the networks formation factors, culminating in obtaining network characterization index and their respective classification. The results indicated that in the studied network there are two groups with different views, culminating in respectives network characterization indices and differents classifications for the two groups. In this way, the work contributes of academy investigating the gap existing of the network construction potential, and in practice, by having a categorized network characterization, being a tool for strategic alignment among the project companies.